Composite opacifier, preparation method and ceramic glaze

By using a combination emulsion agent of zirconium dioxide and zirconium silicate in ceramic glaze and adding calcium phosphate, the radioactivity and high temperature fluidity of zirconium silicate emulsion agent are solved, and the high whiteness of ceramic glaze surface is achieved and high quality.

CN119430642APending Publication Date: 2025-02-14GAOQING YAOSHUO GLAZES TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411331394.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Zirconium silicate has high radioactive radiation as an emulsion agent, and has high viscosity during high temperature sintering and poor fluidity of glaze slurry, resulting in a decrease in whiteness of ceramic glaze surface and an increase in defects.

Method used

A combination of zirconium dioxide and zirconium silicate is used as an emulsion agent, and calcium phosphate is added to form a composite emulsion agent by defining the particle size of zirconium dioxide and zirconium silicate and grinding with dispersion liquid.

Benefits of technology

The better whitening effect of emulsion agent is achieved, the use of zirconium silicate is reduced, the fluidity and glaze quality at high temperatures are improved, and radioactive radiation and glaze defects are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057042560000071
    Figure BDA0005057042560000071
  • Figure BDA0005057042560000081
    Figure BDA0005057042560000081
Patent Text Reader

Abstract

The invention provides a composite opacifier, a preparation method and a ceramic glaze, and relates to the technical field of ceramic glazes. The composite opacifier comprises the following raw material components: zirconium dioxide, zirconium silicate and calcium phosphate, the weight ratio of the zirconium dioxide in the composite opacifier is not more than 10%; the weight ratio of the zirconium silicate in the composite opacifier is 10-50%. Preferably, the composite opacifier can also contain rare earth oxide. The composite opacifier disclosed by the invention is added into glaze, so that a very good whitening effect can be achieved, and the composite opacifier has a relatively good whitening effect under a relatively low dosage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic glazes and relates to a composite opacifier, a preparation method and a ceramic glaze. Background Art

[0002] Zirconium silicate opacifier is a commonly used ceramic glaze whitening agent with the characteristics of high refractive index, white color and good high temperature stability. However, the biggest problem with zirconium silicate as an opacifier is the high radioactive radiation, because the raw material zircon sand contains a small amount of radioactive associated minerals, such as saprolite, zirconium thorium ore and monazite, which are difficult to remove, resulting in the prepared glaze and ceramic products are also radioactive, which is potentially harmful to human health. Reducing the use of zirconium silicate in ceramic glazes can significantly reduce the radioactivity of ceramic glaze products, but it also means that the opacifying performance deteriorates and the whiteness of the ceramic glaze is reduced. In addition, zirconium silicate has high viscosity at high sintering temperatures, poor fluidity of the glaze slurry, and defects are prone to appear on the glaze.

[0003] Therefore, zirconium silicate as an emulsifier requires both reducing its dosage and improving its fluidity at high temperatures, which has become an urgent problem to be solved in the industry. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a composite opacifier, a preparation method and a ceramic glaze.

[0005] The technical solution of the present invention is as follows:

[0006] A composite opacifier, the raw material components of which include zirconium dioxide, zirconium silicate and calcium phosphate;

[0007] The weight proportion of zirconium dioxide in the composite opacifier does not exceed 10%;

[0008] The weight proportion of the zirconium silicate in the composite emulsifier is 10-50%.

[0009] Preferably, the weight proportion of the calcium phosphate in the composite emulsifier is not less than 40%.

[0010] Preferably, the raw material components further contain rare earth oxides.

[0011] More preferably, the weight proportion of the rare earth oxide in the composite emulsifier is 3-10%.

[0012] More preferably, the rare earth oxide is selected from one or a combination of two or more of cerium oxide, lanthanum oxide, yttrium oxide and europium oxide.

[0013] A method for preparing the composite opacifier according to any one of the above embodiments,

[0014] Mixing and grinding the aqueous dispersions of the raw material components to obtain a composite slurry to obtain the composite emulsifier;

[0015] Alternatively, the composite slurry is dried and broken up to obtain the composite emulsifier;

[0016] The D50 particle size of the solid particles in the composite slurry is 0.3-1.5 μm, and the D90 particle size is ≤3 μm.

[0017] Preferably, the concentration of the aqueous dispersion of each of the raw material components is 10-50wt%.

[0018] Preferably, the aqueous dispersion of each of the raw material components independently contains a dispersing aid, and the weight proportion of the dispersing aid in the aqueous dispersion of each of the raw material components independently does not exceed 0.3%.

[0019] More preferably, the dispersant is selected from sodium hexametaphosphate and / or sodium tripolyphosphate.

[0020] A ceramic glaze comprises the composite opacifier described in any one of the above embodiments or the composite opacifier obtained by the preparation method described in any one of the above embodiments.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention uses a combination of zirconium dioxide and zirconium silicate as an opacifier, and the added calcium phosphate further promotes the improvement of the whitening performance of the opacifier, so that the opacifier of the present invention has a good whitening effect, while reducing the amount of zirconium silicate used, and has high fluidity at high temperatures and high glaze quality. In addition, by limiting the particle size of zirconium dioxide and zirconium silicate and using a dispersion grinding method, it is helpful for the raw material components to more fully form a composite opacifier.

[0023] (2) Further adding rare earth oxide to the composite opacifier of the present invention can further improve the whitening effect of the opacifier and the glaze quality. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0025] In order to reduce the amount of zirconium silicate used in the opacifier and improve the fluidity of the glaze at high temperature without affecting the opacifying effect, on the one hand, the present invention provides a composite opacifier, the raw material components of which include zirconium dioxide, zirconium silicate and calcium phosphate;

[0026] The weight percentage of zirconium dioxide in the composite opacifier does not exceed 10%;

[0027] The weight proportion of zirconium silicate in the composite emulsifier is 10-50%.

[0028] Zirconium dioxide and zirconium silicate are both commonly used opacifiers in ceramic glazes, which have a whitening effect. Zirconium dioxide is used alone as an opacifier, and the general addition amount is 10-20wt%. However, the price of zirconium dioxide is much higher than that of zirconium silicate, and such a high addition amount is not economically optimal. When zirconium silicate is used alone, due to the strong radioactive radiation of zirconium silicate, its dosage needs to be reduced. Calcium phosphate is a commonly used glaze raw material, and plays the following roles in glaze: 1) improve the quality of the glaze and reduce defects such as bubbles, bursts, and cracks on the glaze; 2) improve the transparency and brightness of the glaze; 3) increase the hardness and wear resistance of the glaze; 4) improve the chemical stability of the glaze, so that the glaze can resist corrosion from various chemical substances such as acids and alkalis. The present invention unexpectedly found that by adding calcium phosphate to the composite emulsifier and partially replacing zirconium silicate with zirconium dioxide, a better opacifying effect can be achieved at a lower zirconium dioxide content and zirconium silicate content, and the whiteness of the glaze can be improved, and the effect of improving the quality of the glaze can still be maintained. Moreover, compared with zirconium dioxide and / or zirconium silicate alone as an opacifier, the composite opacifier of the present invention has a better opacifying and whitening effect.

[0029] Furthermore, in the composite opacifier of the present invention, the weight proportion of zirconium dioxide in the composite opacifier is not less than 3%. For example, the weight proportion can be any value of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. or any value in between, without special restrictions. For the weight proportion of zirconium silicate in the composite opacifier, for example, it can be any value of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc. or any value in between, without special restrictions.

[0030] In a preferred embodiment of the present invention, the weight proportion of calcium phosphate in the composite emulsion is not less than 40%. For example, the weight proportion of calcium phosphate in the composite emulsion can be any value of 40%, 42%, 44%, 45%, 47%, 48%, 50%, 52%, 54%, 55%, 57%, 58%, 60%, etc. or any value in between, without special limitation. More preferably, the weight proportion of calcium phosphate in the composite emulsion is not higher than 60%.

[0031] In a preferred embodiment of the present invention, the raw material components further include rare earth oxides. Adding an appropriate amount of rare earth oxides to the glaze can improve the whiteness, hardness, wear resistance, thermal shock resistance, etc. of the glaze surface, and some rare earth oxides can also provide antibacterial effects. In the present invention, it is found that adding some rare earth oxides to the composite opacifier can further improve the whiteness of the glaze surface, and the opacifying and whitening effect of the composite opacifier is more obvious, and the quality of the glaze surface can be further improved, and defects such as bubbles, cracks, and cracks on the glaze surface can be reduced.

[0032] If the weight proportion of rare earth oxide in the composite emulsifier is too low, the effect of rare earth oxide cannot be exerted; if the weight proportion of rare earth oxide in the composite emulsifier is too high, it will affect the effect of other raw material components, which is not conducive to the emulsification effect. In a more preferred embodiment of the present invention, the weight proportion of rare earth oxide in the composite emulsifier is 3-10%. For example, the weight proportion can be any value of 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. or any value in between, without special restrictions.

[0033] In a more preferred embodiment of the present invention, the rare earth oxide is selected from one or a combination of two or more of cerium oxide, lanthanum oxide, yttrium oxide and europium oxide. Further preferably, the rare earth oxide is selected from cerium oxide, which has a high cost performance among rare earth oxides and is more economical. Further preferably, the rare earth oxide is selected from white cerium oxide.

[0034] In another aspect, the present invention provides a method for preparing the composite opacifier according to any one of the above embodiments.

[0035] The aqueous dispersions of the raw material components are mixed and ground to obtain a composite slurry to obtain a composite emulsifier;

[0036] Alternatively, the composite slurry is dried and broken up to obtain a composite emulsion;

[0037] The D50 particle size of the solid particles in the composite slurry is 0.3-1.5 μm, and the D90 particle size is ≤3 μm.

[0038] In the present invention, the composite opacifier can exist in the form of slurry or powder, and the solid particles have a particle size within the above range, which can better play the role of the opacifier. Based on the above preparation method, those skilled in the art know that the raw material components can also be added to water together to form an aqueous dispersion and then ground to obtain a composite slurry.

[0039] In a preferred embodiment of the present invention, the concentration of the aqueous dispersion of each raw material component is 10-50wt%. If the concentration of the aqueous dispersion of each raw material component is too low, it is not conducive to actual production and the production efficiency is too low; if the concentration of the aqueous dispersion of each raw material component is too high, the stability may be biased. For example, the concentration of the aqueous dispersion of each raw material component can be any value of 10wt%, 15wt%, 20wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc. or any value in between, without special restrictions.

[0040] In a preferred embodiment of the present invention, the aqueous dispersion of each raw material component contains a dispersing aid independently, and the weight proportion of the dispersing aid in the aqueous dispersion of each raw material component independently does not exceed 0.3%. The inclusion of a dispersing aid in the aqueous dispersion facilitates grinding, and can improve grinding efficiency and uniformity of particle size after grinding.

[0041] In a more preferred embodiment of the present invention, the dispersant is selected from sodium hexametaphosphate and / or sodium tripolyphosphate.

[0042] In yet another aspect, the present invention provides a ceramic glaze comprising the composite opacifier described in any one of the above embodiments or the composite opacifier obtained by the preparation method described in any one of the above embodiments.

[0043] The ceramic glaze of the present invention comprises the above-mentioned composite opacifier, and the weight proportion of the composite opacifier in the ceramic glaze can be 5-16%. The glaze surface after sintering is of high quality, without defects such as bubbles, bursts, and cracks, and has high whiteness. When the composite opacifier is added in an amount of 6wt% (based on the glaze), the whiteness can reach more than 80%; when the composite opacifier is added in an amount of 15wt% (based on the glaze), the whiteness can reach more than 92%. Or preferably, the weight proportion of the composite opacifier of the present invention in the glaze can be 6-10%. The weight proportion of the composite opacifier in the glaze is relatively low, which can further reduce the amount of zirconium silicate used in the glaze, reduce costs, and achieve a better opacifying effect at the same time.

[0044] The technical solution of the present invention is further described and illustrated according to various embodiments below.

[0045] Example 1

[0046] The composite opacifier is composed of 3% zirconium dioxide, 50% zirconium silicate and 47% calcium phosphate in terms of 100% by weight.

[0047] Zirconium dioxide, zirconium silicate and calcium phosphate are added to water respectively, and sodium tripolyphosphate is added at 0.2% by weight of the aqueous dispersion to prepare an aqueous dispersion with a concentration of 40wt%. The aqueous dispersions are mixed according to the proportions of the above raw material components and ground to a D50 particle size of 0.9μm and a D90 particle size of 2.1μm to obtain a composite slurry, which is then dehydrated, dried and dispersed to obtain a composite emulsifier.

[0048] Example 2

[0049] The difference between this embodiment and embodiment 1 is that the raw material components consist of 7% zirconium dioxide, 50% zirconium silicate and 43% calcium phosphate. The other steps remain unchanged.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that the raw material components consist of 10% zirconium dioxide, 50% zirconium silicate and 40% calcium phosphate. The other steps remain unchanged.

[0052] Example 4

[0053] The difference between this embodiment and embodiment 2 is that the raw material components consist of 7% zirconium dioxide, 46% zirconium silicate and 47% calcium phosphate. The other steps remain unchanged.

[0054] Example 5

[0055] The difference between this embodiment and embodiment 3 is that the raw material components consist of 10% zirconium dioxide, 43% zirconium silicate and 47% calcium phosphate. The other steps remain unchanged.

[0056] Example 6

[0057] The difference between this embodiment and embodiment 5 is that the raw material components consist of 10% zirconium dioxide, 30% zirconium silicate and 60% calcium phosphate. The other steps remain unchanged.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 4 is that the raw material components consist of 7% zirconium dioxide and 93% zirconium silicate. The other steps remain unchanged.

[0060] Comparative Example 2

[0061] The difference between this comparative example and Example 4 is that the raw material components consist of 53% zirconium silicate and 47% calcium phosphate. The other steps remain unchanged.

[0062] Comparative Example 3

[0063] The difference between this comparative example and Example 4 is that the raw material component consists of 100% zirconium silicate. The other steps remain unchanged.

[0064] Example 7

[0065] The composite opacifier is composed of 5% zirconium dioxide, 43% zirconium silicate and 52% calcium phosphate in terms of 100% by weight.

[0066] Zirconium dioxide, zirconium silicate and calcium phosphate are added to water respectively, and sodium tripolyphosphate is added at 0.15% by weight of the aqueous dispersion to prepare an aqueous dispersion with a concentration of 30wt%. The aqueous dispersions are mixed according to the proportions of the above raw material components and ground to a D50 particle size of 1.0μm and a D90 particle size of 2.6μm to obtain a composite slurry, which is then dehydrated, dried and dispersed to obtain a composite emulsifier.

[0067] Example 8

[0068] The difference between this embodiment and embodiment 7 is that the raw material components consist of 5% zirconium dioxide, 43% zirconium silicate, 49% calcium phosphate and 3% white cerium oxide. The other steps remain unchanged.

[0069] Example 9

[0070] The difference between this embodiment and embodiment 7 is that the raw material components consist of 5% zirconium dioxide, 43% zirconium silicate, 45% calcium phosphate and 7% white cerium oxide. The other steps remain unchanged.

[0071] Example 10

[0072] The difference between this embodiment and embodiment 9 is that the raw material components consist of 5% zirconium dioxide, 39% zirconium silicate, 49% calcium phosphate and 7% white cerium oxide. The other steps remain unchanged.

[0073] Embodiment 11

[0074] The difference between this embodiment and embodiment 10 is that the raw material components consist of 5% zirconium dioxide, 39% zirconium silicate, 46% calcium phosphate and 10% white cerium oxide. The other steps remain unchanged.

[0075] Performance Testing

[0076] The ceramic glaze consists of a basic glaze and a composite opacifier, and the composite opacifier accounts for 6% by weight in the glaze.

[0077] The basic glaze composition is: 35 parts of quartz, 28 parts of potassium feldspar, 4 parts of aluminum oxide, 14 parts of calcite, 7 parts of dolomite, 3 parts of zinc oxide, 5 parts of kaolin, and 4 parts of frit.

[0078] The main test parameters and conditions for glazing and sintering of the above ceramic glazes are as follows:

[0079] Glaze: ball: water = 1:2:0.6, and 0.1% of methyl cellulose by weight of the glaze is also added.

[0080] Glaze slurry bulk density: 1.70±0.02g; Glaze slurry fluidity: 28-32s; Ball milling time: 18-22h; Glaze slurry fineness: 200 mesh, sieve residue is less than 0.1%; Glaze slurry is sieved twice: 200 mesh and 325 mesh, iron removal twice; Glazing thickness: Glaze is directly applied on the ceramic blank by spraying method. The thickness of the glaze layer before sintering is 0.6-0.8mm.

[0081] Firing in an oxidizing atmosphere, the sintering temperature of the ceramic glaze is 1200-1250℃.

[0082] The whiteness L of the glaze is shown in Table 1 below.

[0083] Table 1

[0084] Whiteness L / % Whiteness L / % Whiteness L / % Example 1 80.5 Example 6 80.3 Example 8 82.6 Example 2 81.3 Comparative Example 1 70.5 Example 9 84.5 Example 3 80.8 Comparative Example 2 72.2 Example 10 83.0 Example 4 82.2 Comparative Example 3 68.7 Embodiment 11 81.4 Example 5 81.4 Example 7 80.7

[0085] It can be seen from the data results in Table 1 above that the composite opacifier of the present invention has a good whitening effect in the glaze, and has a better whitening effect than single zirconium silicate.

[0086] The composite opacifiers of Example 4, Comparative Examples 1-3 and Examples 7-8 were selected, and their weight proportions in the glaze were 5%, 10% and 15% respectively, and the test was carried out according to the above performance test method. The whiteness L of the glaze is shown in Table 2 below.

[0087] Table 2 Whiteness L / %

[0088]

[0089]

[0090] It can be seen from the data in Table 2 that the composite opacifier of the present invention has a good whitening effect when used in a relatively low amount (5%). When the added amount reaches 10%, the whiteness of the glaze layer can reach 90% or more. When the added amount reaches 15%, the whiteness of the glaze layer can reach 92% or more.

[0091] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

Claims

1. A composite emulsifier, characterized in that: The raw material components include zirconium dioxide, zirconium silicate and calcium phosphate; The weight proportion of zirconium dioxide in the composite opacifier does not exceed 10%; The weight proportion of the zirconium silicate in the composite emulsifier is 10-50%.

2. The composite opacifying agent according to claim 1, characterized in that The weight proportion of the calcium phosphate in the composite emulsifier is not less than 40%.

3. The composite opacifying agent according to claim 1, characterized in that: The raw material components further include rare earth oxides.

4. The composite opacifying agent according to claim 3, characterized in that: The weight proportion of the rare earth oxide in the composite emulsifier is 3-10%.

5. The composite opacifying agent according to claim 3, characterized in that: The rare earth oxide is selected from one or a combination of two or more of cerium oxide, lanthanum oxide, yttrium oxide and europium oxide.

6. A method for preparing the composite opacifier according to any one of claims 1 to 5, characterized in that: Mixing and grinding the aqueous dispersions of the raw material components to obtain a composite slurry to obtain the composite emulsifier; Alternatively, the composite slurry is dried and broken up to obtain the composite emulsifier; The D50 particle size of the solid particles in the composite slurry is 0.3-1.5 μm, and the D90 particle size is ≤3 μm.

7. The method for preparing the composite opacifier according to claim 6, characterized in that: The concentration of the aqueous dispersion of each of the raw material components is 10-50 wt %.

8. The method for preparing the composite opacifier according to claim 6, characterized in that: The aqueous dispersion of each of the raw material components independently contains a dispersing aid, and the weight proportion of the dispersing aid in the aqueous dispersion of each of the raw material components independently does not exceed 0.3%.

9. The method for preparing an opacifying agent according to claim 7, characterized in that: The dispersant is selected from sodium hexametaphosphate and / or sodium tripolyphosphate.

10. A ceramic glaze, characterized in that: The invention comprises the composite emulsion according to any one of claims 1 to 5 or the composite emulsion prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Emulsion whitening agent for ceramic and preparation method thereof

    CN103880475A

  • Zirconium white fritted glaze and preparation method thereof

    CN105314849A

  • Ceramic whitening agent as well as preparation method and application thereof

    CN110950535A

  • Super stain-resistant ceramic tile color-retaining glaze, stain-resistant ceramic tile and preparation process of stain-resistant ceramic tile

    CN111170638A

  • Ultra-white fabric, ultra-white luxury ceramic rock plate and preparation method thereof

    CN118652101A